TESIS ANALISIS STRATEGI DINAS KEBUDAYAAN PARIWISATA, PEMUDA DAN OLAH RAGA DALAM PENGEMBANGAN PARIWISATA DI KABUPATEN PONOROGO: JURNAL TESIS - Binarpendyah Rawitri HS; Joko Pramono; Aris Tri Haryanto (Master of Public Administration, Universitas Slamet Riyadi, 2022)
The results of the study show the S-O Strategy, which is to develop and increasetourist attraction with various potentials, such as the typical socio-culturalconditions of the community. S-T strategy, by utilizing good information media toattract investors. This is done by providing accurate information about theleading potential of tourism. W-O strategy, namely with stable politicalconditions, it is hoped that the Culture and Tourism Office will be able to involvepower holders so that they are willing to provide assistance in improving humanresources both in quality and quantity. Threats are facilities and infrastructurethat are tools to support the success of an effort process carried out in publicservices, because if these two things are not available then all activities carriedout will not be able to achieve the expected results according to the plan.Keywords: Tourism development strategy of the Department of Culture,Tourism, Youth and Sports, Ponorogo Regency